Unilateral Intervention in the Sinuses of Rabbits Induces Bilateral Inflammatory and Microbial Changes - Lux, Christian A.; Johnston, James J.; Waldvogel-Thurlow, Sharon; Dassi, Camila; Douglas, Richard G.; Cho, Do-Yeon; Taylor, Michael W.; Biswas, Kristi (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Chronic rhinosinusitis (CRS) is a globally prevalent inflammatory condition of the paranasal sinuses which severely impairs patients’ quality of life. An animal model of unilateral sinusitis by transient sinus occlusion has been described previously in rabbits. The aim of this study was to characterise the sinusitis rabbit model by investigating temporal and bilateral changes in the bacterial community and mucosal inflammation. Methods: Development of sinusitis was achieved by endoscopically placing Merocel®, a sterile nasal packing material, in the left middle meatus of six New Zealand white rabbits for four weeks. After a total period of 14 weeks, rabbits were assessed for sinusitis by endoscopic examination, magnetic resonance imaging (MRI) and histology. Swabs from the left and right middle meatus were obtained for bacterial community analysis at three time points (week 0, week 4, week 14) during the study. Results: Endoscopic evaluation showed unilateral inflammation in all animals examined after the 4-week blocking period and at week 14. Notably, inflammatory changes were also seen in the contralateral sinus of all animals at week 4. MRI images demonstrated unilateral sinus opacification at week 4 in two rabbits, and partial unilateral sinus opacification at week 14 in one rabbit only. Histological analyses revealed substantial spatial heterogeneity of mucosal inflammation with inconsistent findings across all animals. No significant differences in mucosal inflammatory markers could be identified between nostrils at week 14. The bacterial community in the rabbit sinuses was heavily dominated by Helicobacter at week 0 (baseline). At the end of the blocking period (week 4), bacterial alpha and beta diversity were significantly increased in both nostrils. The bacterial community composition at week 14 had primarily returned to baseline, reflecting the endoscopic and radiological results. Conclusion: This study reaffirmed the ability for development of sinusitis without inoculation of any pathogens in a rabbit model. We were able to demonstrate bilateral sinonasal mucosal inflammation, by inducing unilateral sinus blockage, which resulted in significant changes to the sinonasal bacterial community. These findings may explain some of the clinical observations seen in CRS and have significant implications for future studies and developing therapeutic management.